Investigation of safety leadership within infrastructure engineering construction projects - Stiles, Shelley (2019)
The Infrastructure Engineering Sector of the Construction Industry is one of the high-risk sectors of work in the UK (HSE 2009), where engineering and construction activities that either enhance or maintain the rail and public highway infrastructure are undertaken in a hazardous environment. Occupational health and safety performance data is showing that the industry performance has reached a plateau; to achieve the next step change in improved performance it is necessary to tackle behaviours and culture. The work of the Infrastructure Engineering Industry is largely delivered through a small number of Principal Contractors, with procured second and third tier contracting organisations to deliver specialist works. Through the identification of Principal Contractors as leaders of project delivery, a common project organisation structure is developed – referred to as ‘Project Delivery Organisation’. The structure of a Project Delivery Organisation may impact on safety culture for various reasons, in particular the organisation and interfaces between these different parties. Whilst there is considerable research on the characteristics of positive and negative safety cultures, research to date does not consider the interfaces and relationships between different organisations that are co-ordinated to work together for a determined period of time forming a quasi-organisation such as a Project Delivery Organisation. With recognition of a multitude of factors that can influence safety culture, the thesis evaluates the factors influencing safety on typical construction projects to understand the impact on overall safety performance and seeks ways to enhance safety through leadership programmes. The thesis aims to investigate safety leadership within the Infrastructure Engineering Sector of the Construction Industry to determine whether safety leadership is important for improving the safety culture of a construction project. The thesis builds upon the areas identified from existing research into safety, safety leadership and safety culture, and applies these theories in specific application to better understand the components, factors and interactions that influence safety, safety culture and safety leadership within a Project Delivery Organisation, and to evaluate the effectiveness of safety leadership interventions within a Project Delivery Organisation making recommendations for industry. This thesis investigates safety leadership within Project Delivery Organisations taking a multi-method approach across four separate studies which: • evaluate perceptions of safety culture (Study 1) • establish the contents of existing Safety Improvement Programmes (Study 2) • evaluate attitudes to safety leadership (Study 3) • deploy a safety leadership intervention tool and identify factors influencing safety leadership interventions on projects (Study 4) Study 1 involved holding a number of workshops were held to establish perceptions of safety culture maturity amongst two groups: Principal Contractors and their Supply Chain. Participants were asked to rank their safety culture maturity and that of the other group on a maturity scale of 1-5, with 5 being the most mature. This study found that there was a significant difference in the perceived safety culture maturity of the Principal Contractor and Supply Chain, with Principal Contractors perceived as more mature that the Supply Chain. Study 2 sought to understand what Safety Improvement Programmes were adopted within the Supply Chain. An anonymous questionnaire survey was issued to Supply Chain organisations posing questions relating to safety improvements, initiatives, their content and purpose. This study found that whilst Principal Contractors were implementing Safety Improvement Programmes on construction projects, their effectiveness was being diluted by the Supply Chain with their non-application of these programmes within their own organisation. Study 3 focused on attitudes to safety leadership within the rail construction sector. Twenty-one in-depth interviews were undertaken with representatives from Client, Principal Contractor and Supply Chain, to identify attitudes to safety leadership and consider how this may impact on safety performance. The level of understanding of safety leadership as a topic was evaluated against how well the study participants could explain the concept, and whether they could provide any examples of real-world application. This study found that there are numerous safety leadership interventions being deployed on these projects. Half of the intervention examples provided were based around communication activities. The likely success of these leadership interventions will be influenced by five themes; context, preparation, communication, leadership behaviour and style, and action. From Studies 1, 2 and 3 a model of a Project Delivery Organisation was established showing the relationships between the different member organisations as well as identifying potential influencing factors. In preparation for Study 4, a Safety Leadership Intervention Tool (SLIT) was developed as part of this research based on existing safety culture, safety performance and leadership research, and the researchers experience within industry. The SLIT was designed to provide consistent resources to participating projects and each Project Management team to achieve a positive change in safety outcomes for the duration of the project, utilising techniques that demonstrate safety leadership. The SLIT design is a particular contribution from this thesis. Study 4 investigated the implementation of a Safety Leadership Intervention Tool (SLIT) across six Project Delivery Organisations, three different Project Delivery Organisations in the Intervention Group and a further three Project Delivery Organisations in the Baseline Group for comparison purposes. A multi-methods approach was undertaken within Study 4 with data collected using interviews, surveys and a review of project safety records. A logic map was used as the evaluation framework for determining the effectiveness of the safety leadership interventions for each project. The same logic map is also used to compare findings for the two groups of case studies – baseline and intervention groups. From this study it can be concluded that Project Delivery Organisations are reluctant to implement new safety interventions as SLIT interventions were only partially implemented. Two main influencing factors have been found to affect safety performance within a Project Delivery Organisation. The influence of the Client representatives and Project Manager can have a positive or negative impact on the safety culture maturity, depending on whether they demonstrate good role model behaviours or not. Situational constraints have also been found to impact on the effectiveness of safety leadership interventions within a project environment. This was particularly evident when there was a greater focus on delivering the project to a specified timescale/deadline. The thesis makes a number of contributions from the research that has been undertaken and builds upon existing research relating to: • safety performance (Mearns et al 2003, DeJoy et al 2004, Grabowski et al 2007, Hale et al 2010, Walters and James 2009, Winkler and Irwin 2003) • safety culture (Fleming 2001, Fleming and Lardner 2008, Cooper 2001, Parker et al 2006, Zohar 1980, 2002) • safety leadership (Hopkins 2006, Fleming and Lardner 2001, Hofmann et al 1995, Shannon et al 1997) The thesis findings are applied to construction projects, as dynamic transient environments where organisations are contracted to work together for a defined and limited period of time forming a quasi-organisation. The main findings relate to: • The importance of safety leadership behaviours on a construction project and identification that there is still further work needed to develop individual safety leadership skills particularly relating to change efficacy. A key finding was that how an intervention is implemented is equally as important as the content of the intervention itself. • Understanding the two main influencing factors that can impact on the effectiveness of safety leadership interventions within a Project Delivery Organisation. These are Client behaviour and situational constraints associated with increased role demands. • Understanding the safety culture maturity within a Project Delivery Organisation, where Principal Contractors are perceived to be more mature than the Supply Chain. The thesis adopted many well-established techniques for data collection and evaluation taking a multi-methods approach. The thesis has made a specific methodological contribution for future studies seeking to evaluate interventions through the use of a logic map for both intervention design and evaluation. A logic mapping approach can be taken to inform the data collection, collation and analysis of relationships across a wide range of data sources. Whilst the methodological approach was a contribution, the complexity of Study 4 is also a limitation. The two different groups of projects (Intervention and Baseline) participating in Study 4 was also considered a potential limitation. The study design was to create a control (Baseline Group) for comparison with the Intervention Group projects. However, it may have been more appropriate to compare the implementation of the SLIT across more projects – all being in the Intervention Group and not have a control group. The sampling approach taken for the participating projects was a potential limitation. There was limited access and availability to the researcher for selecting projects to participate in Study 4 whilst resulted in too wide a range of different size of projects (measured via project duration, value and appointed resources) participating in the study. In future studies it is recommended that specific consideration should be given to project size when looking to compare between projects. The thesis used perceptions to establish views towards safety, safety culture and safety leadership across several studies (1, 3, 4). However, the focused was on the relationship between Principal Contractor and the Supply Chain. The lack of Client perceptions within Studies 1 and 4 is a limitation. In future studies it would be prudent to include the Client attitudes towards safety. This research investigated safety leadership within Infrastructure Engineering Projects in the Construction Industry. Further studies could evaluate in more depth the factors influencing safety performance within a Project Delivery Organisation including the impact of Client behaviours towards safety, identification of individuals as leaders of safety within a construction project and how this role is deployed in practice, and an evaluation of change management frameworks for the implementation of Safety Improvement Programmes.